An analysis of the effectiveness of Corporate Social Responsibility in the mining sector: a comparative study of South Africa and Zimbabwe mining companies - Mandevere, Melody (My University, 2021)
Over the past years, Corporate Social Responsibility (CSR) has received increased attention from the corporate world and international organisations. There has been a call for an Africanised CSR agenda based on the African context since CSR activities being undertaken in developing countries do not address the root cause of poverty and fail to improve relations with local communities. There is concern over the sustainability of the CSR projects undertaken by mining companies in Zimbabwe and the motives behind CSR activities aimed at benefitting the mining companies’ shareholders and less on the community where they operate. CSR projects in Zimbabwe differ to that of South Africa although the companies are subsidiaries. This comparative study between Zimbabwe and South Africa’s mining sectors has been carried out to analyse the effectiveness of Corporate Social Responsibility activities. The study followed the interpretivism philosophy and the qualitative research design with multiple case studies in the two countries. The target population for the research were two companies with branches in Zimbabwe and South Africa. Hence four mines were chosen, two in Zimbabwe and two in South Africa. A total of 22 respondents were purposively selected consisting of community representatives, mining company representatives, non-governmental stakeholders and governmental stakeholders. Data was triangulated by integrating semi-structured interviews and secondary documents. The findings indicated that in South Africa there is more stakeholder inclusion and ownership of the CSR projects as compared to Zimbabwe. This is more attributed to the nature of the South African legislation on CSR that encourages stakeholder inclusion. The stakeholder inclusion and ownership contributes to project sustainability which then leads to effectiveness of CSR. The research also concluded that an Africanised CSR agenda should prioritize legal issues over others. This means African countries need to attend to their legislation so that CSR is mandatory with ‘social impact’ as the driving force. The study contributes to the CSR literature specifically as a comparative study between African countries. This is one of the few empirical studies that compare CSR in neighbouring developing countries. Moreover, the study also addresses whether there is a need for a more Africanised CSR to address the social challenges and understand the effectiveness of the Africanised CSR agenda leading to sustainable development
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy (PhD), 2021
Keywords: UCTD; Corporate Social Responsibility; Mining Sector; South Africa; Zimbabwe; Mining; SDG-8: Decent work and economic growth